1984
DOI: 10.1007/bf00382079
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the 16S-23S spacer region in the rrnA operon from a blue-green alga, Anacystis nidulans

Abstract: The nucleotide sequence of a spacer region between 16S and 23S rRNA genes from tobacco chloroplasts has been determined. The spacer region is 2080 bp long and encodes tRNA Ile and tRNA A la genes which contain intervening sequences of 707 bp and 710 bp, respectively. Strong homology between the two intervening sequences is observed. These spacer tRNAs are synthesized as part of an 8.2 kb precursor molecule containing 16S and 23S rRNA sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…2 contains genes coding for tRNA ' and tRNA*'", as observed in several eubacteria including the cyanobacterium Synecbococcw sp. strain PCC 6301 (Tomioka & Sugiura, 1984), and in plastids (Graf etal., 1980;Ohyama etal., 1986). In six out of the eight independently sequenced clones, it shows a duplication of 29 nucleotides involving 14 nucleotides upstream of the tRNA1le and the first 15 nucleotides of the tRNA1le.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 contains genes coding for tRNA ' and tRNA*'", as observed in several eubacteria including the cyanobacterium Synecbococcw sp. strain PCC 6301 (Tomioka & Sugiura, 1984), and in plastids (Graf etal., 1980;Ohyama etal., 1986). In six out of the eight independently sequenced clones, it shows a duplication of 29 nucleotides involving 14 nucleotides upstream of the tRNA1le and the first 15 nucleotides of the tRNA1le.…”
Section: Resultsmentioning
confidence: 99%
“…has not been determined because prohibitive amounts of pure D N A would be necessary but two, five and six copies were observed for other cyanobacteria (Nichols e t al., 1982). The first 395 nucleotides from the two copies of the ITS of S'nechococczis PCC 6301 have been sequenced independently (Williamson & Doolittle, 1983;Tomioka & Sugiura, 1984). Only four insertions and two deletions were observed, and Tomioka & Sugiura (1 984) concluded that the rm operons were highly conserved.…”
Section: Resultsmentioning
confidence: 99%
“…The ITSs within each copy are identical in length and in sequence, and the two copies therefore encode the same tRNA gene(s). Similarly, the two ITS regions of Synechococcus PCC 6301 show only six differences in the 395 nucleotides (representing 72 % of the sequence and including both tRNA genes) available for comparison (Williamson & Doolittle, 1983 ;Tomioka & Sugiura, 1984).…”
Section: Two Different Its Regions (Its-l and Its-s)mentioning
confidence: 99%
“…Limited data have been obtained from the physical or genetic maps of the unicellular strains Synechococcus PCC 6301 (Tomioka et al, 1981), Synechococcus PCC 7002 (Chen & Widger, 1993) and Synechocystis PCC 6803 (Kaneko et al, 1996). Further information is available from the sequences of the 16S rRNA-23S rRNA ITS domain in members of several cyanobacterial genera that include the unicellular Synechococcus PCC 6301 (Tomioka & Sugiura, 1984), Synechocystis PCC 6803 (Kaneko et al, 1996) and 47 strains of the genus Microcystis (Otsuka et al, 1999), the filamentous (non-heterocystous) Arthrospira PCC 7345 (Nelissen et al, 1994), Spirulina PCC 6313 (Nelissen et al, 1994) and Trichodesmium NIBB 1067 , the heterocystous Nodularia BCNOD 9427 (Hayes & Barker, 1997) and a strain of uncertain generic identity, ' Mastigocladus HTF ' strain PCC 7518 (G. Van der Auwera & A. Wilmotte, personal communication). In addition, the sequence of the ITS of the photosynthetic cyanelle of Cyanophora paradoxa has been determined (Janssen et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these regions have been shown to encode tRNAs in some rRNA gene clusters. In the intergenic spacer, a glutamate tRNA or tandem isoleucinealanine tRNAs may be encoded (5,9,13,14,22,25). Some distal spacers have been shown to encode an aspartate and/or a tryptophan tRNA or a threonine tRNA (3,9,17 Southern hybridization analysis of rRNA and spacer tRNA genes.…”
mentioning
confidence: 99%